2016
DOI: 10.1093/jxb/erw453
|View full text |Cite
|
Sign up to set email alerts
|

The apoplasmic pathway via the root apex and lateral roots contributes to Cd hyperaccumulation in the hyperaccumulatorSedum alfredii

Abstract: HighlightA portion of the cadmium taken up by the hyperaccumulator Sedum alfredii can be apoplasmically transported to the xylem via root apexes and lateral roots, where the suberin lamellae are not well developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 70 publications
(106 reference statements)
4
35
0
Order By: Relevance
“…Most of early literatures pointed out that transporter‐mediated symplastic and coupled transcellular pathways were the only pathways for Cd influx (Lu et al, ; Van der Vliet, Peterson, & Hale, ; Zhao, Hamon, Lombi, McLaughlin, & McGrath, ) whereas the apoplastic pathway was associated with low importance for radial transport of Cd. Nevertheless, our recent study demonstrated that up to 37% of all Cd ions could directly move to the xylem of a hyperaccumulating ecotype of Sedum alfredii via the apoplastic pathway, and relative proportions of Cd taken up through apoplastic pathway were substantially higher in the hyperaccumulating than in the nonhyperaccumulating ecotype (Tao et al, ). However, the physiological and molecular mechanisms leading to the large intraspecific differences in contribution of apoplastic pathway to Cd uptake are not clear.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Most of early literatures pointed out that transporter‐mediated symplastic and coupled transcellular pathways were the only pathways for Cd influx (Lu et al, ; Van der Vliet, Peterson, & Hale, ; Zhao, Hamon, Lombi, McLaughlin, & McGrath, ) whereas the apoplastic pathway was associated with low importance for radial transport of Cd. Nevertheless, our recent study demonstrated that up to 37% of all Cd ions could directly move to the xylem of a hyperaccumulating ecotype of Sedum alfredii via the apoplastic pathway, and relative proportions of Cd taken up through apoplastic pathway were substantially higher in the hyperaccumulating than in the nonhyperaccumulating ecotype (Tao et al, ). However, the physiological and molecular mechanisms leading to the large intraspecific differences in contribution of apoplastic pathway to Cd uptake are not clear.…”
Section: Introductionmentioning
confidence: 95%
“…Cd‐hyperaccumulators, plants possessing the ability to tolerate and accumulate high concentrations of Cd, are of great potential for phytoremediation of Cd‐contaminated soils (Krämer, ; Zhao, Jiang, Dunham, & McGrath, ). To date, several processes determining the efficiency of Cd hyperaccumulation have been documented, including increased mobilization of Cd in rhizosphere (Li et al, ), facilitated radial transport in roots (Tao et al, ), enhanced long‐distance transport in xylem (Lu et al, ), and effective sequestration and detoxification in shoot (Tian et al, ). From those processes, radial transport in roots is crucial to the accumulation of Cd in the aboveground organs, because it determines the amount of Cd ions moving from epidermis to stele (Belimov et al, ; Lux, Martinka, Vaculík, & White, ; Tao et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations